Ovarian development of female mud crab, Scylla serrata supplemented with cholesterol and injected with serotonin - Betsy J. Pattiasina; M. Zairin Junior; I. Mokoginta; R. Affandi; W. Manalu (Jurnal Akuakultur Indonesia)
Cholesterol is known to play an important role in nutrition of crustacean and function as a precursor for steroids synthesis, while neurohormone of serotonin could induce ovarian maturation in crustacean. Ovarian development of adult females Scylla serrata was induced by adding cholesterol in the diet and serotonin injection. This research was designed to study the effectiveness of cholesterol supplementation and serotonin injection in ovarian development. Broodstocks were stocked in nine experimental units in three fiber tanks. The fiber tank was equipped with sands substrate and flow through seawater system. The experimental crabs were assigned into a completely randomized design with a 3 x 3 factorial arrangement. The first factor was cholesterol supplementation in the diet with 3 levels (0, 0,5 and 1,0%). The second factor was serotonin injection with 3 levels (0, 5 and 10 μg/g BW). Samples of broodstock were taken every four days to evaluate the stages of ovarian maturity and parameters were used to evaluate the ovarian maturation stage are gonad index (GI) and oocyte diameter, concentration of estradiol 17β, yolk protein concentrations, and fecundity. Results showed that female crabs supplemented with 0,5% cholesterol and a combination of cholesterol 0,5% supplementation and injection serotonin with a dose of 10 μg/g BW had better reproduction development. It is concluded that ovarian development of Scylla serrata could be improved by cholesterol supplementation and serotonin injection.